Self-generated off-axis holography in interferometric out-of-focus imaging of ice particles. Issue 1 (2nd January 2019) - Talbi, Mohamed; Gréhan, Gérard; Coëtmellec, Sébastien; Brunel, Marc
ABSTRACT: Interferometric out-of-focus imaging of ice particles is realized. A review of the recent developments performed to analyse the speckle-like out-of-focus images of rough particles is first proposed. A remaining challenge is the analysis of overlapping out-of-focus images. In a second part, the overlapping defocused images of two nearby ice particles are analysed. If one particle is much smaller than the other one, the pattern constitutes an off-axis hologram whose analysis gives the exact size and shape of the biggest particle. Using two angles of view, we obtain a 3D description of the biggest ice particle.